Effect of high-intensity interval training and moderate-intensity continuous training with quercetin supplementation on the mitochondrial gene expression in the diabetic heart - Mojdeh Khajehlandi; Lotfali Bolboli (Jorjani Biomedicine Journal)
Background: Mitochondrial function is an integral part of glucose-stimulated insulin secretion in pancreatic β-cells and is a hallmark feature of cardiovascular disease. It may contribute to the pathophysiology of diabetic cardiomyopathy and atherosclerosis. This study aimed to investigate the effect of high-intensity interval training (HIIT) and moderate-intensity continuous training (MICT), combined with quercetin supplementation (eight weeks), on mitochondrial gene expression in the diabetic heart. Methods: In this study, 35 adult male rats were equally divided into seven groups (n=5): healthy sedentary, diabetic sedentary, diabetic quercetin sedentary, diabetic HIIT (DHIIT), diabetic MICT (DMICT), DHIIT with quercetin, and DMICT with quercetin. The rats were fed a high-fat diet for eight weeks and subsequently treated with a single low dose of streptozotocin to create a model of type 2 diabetes mellitus (T2DM). Eight weeks (five times a week) of HIIT and MICT, with and without quercetin, were conducted for the training groups, and quercetin was injected over eight weeks at a dose of 15 mg/kg. Results: Eight weeks of quercetin supplementation, HIIT, and MICT, with and without quercetin, significantly decreased blood glucose levels (P=0.001). Eight weeks of HIIT and MICT training increased nuclear respiratory factor-2 (NRF2) (P=0.001) and adipose triglyceride lipase (ATGL) (P=0.001) expression and decreased perilipin 2 (PLIN2) gene expression (P=0.001). Conclusion: The training groups alone improved the gene expression of NRF2, ATGL, and PLIN2. Both training protocols, combined with quercetin, controlled blood glucose levels and improved antioxidant capacity. Thus, the reduction in blood glucose through quercetin supplementation appears to be a promising approach for managing T2DM.